2015
DOI: 10.4172/2155-9627.1000225
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics of Glioblastoma Multiforme

Abstract: Aberrations in the epigenetic machinery of the genome may results the inactivation of critical genes and the epigenetic changes are important mechanisms in the evolution of malignancies that not only contributes to tumorigenesis but may also precede genetic changes. Several epigenetic mechanisms have been observed in glioblastomas including DNA hyper-methylation of genes, histone modifications including methylation and acetylation, nucleosomal rearrangement and dysregulation of noncoding RNA expression have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
1
2
0
Order By: Relevance
“…al., 2011;Caffo et. al., 2014;Rasime 2015;Ghosh et al, 2017]. Present study showed high increase of methylation pattern in glioma tissue of higher grades with clustered enhanced DNMT1 expression at protein levels which has also been re ected in mRNA production level, but here the difference is less (Fig.…”
Section: Discussionsupporting
confidence: 47%
“…al., 2011;Caffo et. al., 2014;Rasime 2015;Ghosh et al, 2017]. Present study showed high increase of methylation pattern in glioma tissue of higher grades with clustered enhanced DNMT1 expression at protein levels which has also been re ected in mRNA production level, but here the difference is less (Fig.…”
Section: Discussionsupporting
confidence: 47%
“…IGF2, IL-8) renders "epimutational" correlation with increased invasion, therapeutic escaping and abnormal proliferative nature of glioma [86,[88][89][90] . recent findings also suggest that epigenetic alterations are somehow linked to somatic gene abnormalities [87] .…”
Section: Cellular Alterations: Epigenetic Reprogrammingmentioning
confidence: 99%
“…SOCS1, SOCS2) and silencing genes associated with DNA repair mechanism (e.g. MGMT) [84][85][86][87] . Interestingly on the other hand, hypomethylation-oriented up-regulation of genes causing invasiveness (e.g.…”
Section: Cellular Alterations: Epigenetic Reprogrammingmentioning
confidence: 99%